EVALUASI PROGRAM SISTEM PERINGATAN DINI PENGENDALIAN PENDUDUK (SIPERINDU) DALAM PENGENDALIAN KEPENDUDUKAN PERWAKILAN BKKBN PROVINSI RIAU TAHUN 2022-2024 - Mayritan, Alrahni; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Population issues are fundamental issues that have a direct impact on various aspects of life, from economics, social, politics, to the environment. Population is both the subject and object of development, so the success of national development is largely determined by how the government is able to manage the growth, distribution, and quality of its population. The SiPerindu application was created as an early warning tool for population problems, especially in Riau Province. This study aims to evaluate the Population Control Early Warning System Program (SiPerindu) by the Riau Province BKKBN Representative in 2022–2024 and analyze its impact on population control. This study uses a descriptive qualitative method with data collection techniques through interviews and documentation with related parties, such as the Riau Province BKKBN Representative, DP3AP2KB Riau Province, DPPKB Pekanbaru City, and the Chairperson of the Population Coalition. The theory used is the program evaluation theory by William N. Dunn which includes 6 indicators, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of this study indicate that the implementation of SiPerindu has not been optimal across all evaluation indicators. The main obstacles include limited human resources, lack of budget, missing data and infrastructure, and weak data integration between agencies. Despite this, the SiPerindu application has been used as a basis for the development of the Population Development Grand Design (GDPK) and the Roadmap For Population Development (PJPK). SiPerindu is also considered quite responsive in providing population data and has received positive feedback from the public. However, improvements in data updating and accessibility are still needed. Keywords: Program Evaluation, SiPerindu, Population Control, BKKBN.